Alih Kode Dalam Drama Series Scandal 2: Sex, Love, And Revenge - Sesa Ajulita; Patrisia Cuesdeyeni; Yuliati Eka Asi; Lazarus Linarto; Rusmina Rusmina; Argumen Argumen (Universitas Palan, 2023)
The aim of this research is (1) to describe the factors causing code switching in the Drama Series Scandal 2: Sex, Love, and Revenge. (2) describe the function of using code switching in the Drama Series Scandal 2: Sex, Love, and Revenge. This research is qualitative descriptive research. The subject of this research is speech events that occurred in the Drama Series Scandal 2: Sex, Love, and Revenge. The object of this research is data containing code switching in speech events in the Drama Series Scandal 2: Sex, Love, and Revenge. The technique used in collecting data uses non-participating listening and note-taking techniques. Data were analyzed using qualitative descriptive methods with data transcription and data classification steps. The validity of the data is obtained through continuous data searching according to the facts, persistent observation techniques, and triangulation. The results of this study show two conclusions. First, there are five factors that cause code switching in Drama Series Scandal 2: Sex, Love, and Revenge, namely the speaker, the interlocutor, the presence of a third speaker, the subject of discussion, and to evoke a sense of humor, and simply to have agency. Second, there are five functions of code switching in Drama Series Scandal 2: Sex, Love, and Revenge, namely explaining, asking, reprimanding. Affirm and remind